2020
DOI: 10.3389/fonc.2020.613679
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Beclin 1 Expression in Gastric Cancer: A Marker for Carcinogenesis, Aggressive Behaviors and Favorable Prognosis, and a Target of Gene Therapy

Abstract: Beclin 1 is encoded by Becn1, and plays a role in tumorigenesis, neurodegeneration, apoptosis and autophagy. Here, the aggressive phenotypes and relevant proteins were examined after Beclin 1 expression was altered in gastric cancer cells. We also observed the effects of Beclin 1 on gastric carcinogenesis using Becn1 knockout mice. Finally, clinicopathological significances of Beclin 1 expression were analyzed using meta- and bioinformatics analyses. Becn1 overexpression was found to inhibit proliferation, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…Downregulation of Beclin-1 is correlated to the incremental reprogramming in glucose metabolism, cell invasion and proliferation in gastric cancer. Specifically, reduced Beclin-1 expression increases lymph node metastasis and is associated with poor prognosis [ 161 ]. When comparing tissue samples from Colorectal Cancers (CRCs) to normal colon tissue, Beclin-1 was downregulated in the CRC tissue, which promoted CRC cell invasion [ 162 ].…”
Section: Autophagy and Its Dual Role In The Regulation Of Cancermentioning
confidence: 99%
“…Downregulation of Beclin-1 is correlated to the incremental reprogramming in glucose metabolism, cell invasion and proliferation in gastric cancer. Specifically, reduced Beclin-1 expression increases lymph node metastasis and is associated with poor prognosis [ 161 ]. When comparing tissue samples from Colorectal Cancers (CRCs) to normal colon tissue, Beclin-1 was downregulated in the CRC tissue, which promoted CRC cell invasion [ 162 ].…”
Section: Autophagy and Its Dual Role In The Regulation Of Cancermentioning
confidence: 99%
“…TGF-b is an important representative of the TGF-b family, which includes 3 subtypes (b1, b2 and b3). TGF-b1 was first discovered in lymphocytes and monocytes, which is the most common form of TGF-b (Zheng et al, 2020). The TGF-b signaling pathway is connected with the angiogenesis, invasion, metastasis in gastric cancer (Yue and Mulder, 2001).…”
Section: The Tgf-b Pathwaymentioning
confidence: 99%
“…Autophagy plays also tumor-suppressor and tumor-promoter role in gastric cancer [18]. Autophagy-related markers as Beclin1 might be considered as a potential marker of gastric carcinogenesis, aggressiveness and prognostic prediction, and as a target for gene therapy in gastric cancer [19] while autophagy inducers, such as rapamycin, show promise for gastric cancer treatment [20]. It was also reported that long-term Helicobacter pylori infection can disrupt autophagy process eventually promoting gastric cancer [21].…”
Section: Discussionmentioning
confidence: 99%